Assertivitas Mahasiswa Berkebutuhan Khusus Dalam Mengakses Layanan Perpustakaan - Ni Ketut Ayu Nirmala Dewi; Zulaikha, Sri Rohyanti; Perdana, Diyan Rizki (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to identify the level of assertiveness among students with special needs in accessing information services at the Library of UIN Sunan Kalijaga Yogyakarta. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The findings indicate that students with disabilities demonstrate assertive behaviors through their ability to express information needs clearly, maintain self-respect while respecting others, and assertively decline requests that do not align with their comfort or capacity. Additionally, librarians implement several service strategies, including inclusive service training, the provision of accessibility facilities, managerial support, and the promotion of awareness among the academic community regarding disability-inclusive services. The study concludes that the assertiveness of students with disabilities grows alongside responsive services, supportive environments, and positive interactions between users and librarians. The implication of this research highlights the need to strengthen inclusive service policies, particularly in digital accessibility, enhance librarians’ competencies in serving users with disabilities, and conduct regular evaluations to ensure that information needs of all users are equitably met.